Cancer in the Arab World 2022
DOI: 10.1007/978-981-16-7945-2_9
|View full text |Cite
|
Sign up to set email alerts
|

General Oncology Care in Libya

Abstract: Libya is a large country, ranking at fourth in terms of area both in the Arab world and the African continent (https://www.worldatlas.com/articles/which-are-the-10-largest-countries-of-africa-by-size.html). It is part of the World Health Organization–Eastern Mediterranean Regional Office (WHO–EMRO) region. Oil production is the main source of income which has transformed the country massively over the past 50 years and the healthcare system is one of the sectors that have improved significantly. The Health Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In absence of a well-established national Libyan cancer registry ( 12 ), the results of this study might lay the groundwork for the drafting and development of a cancer care strategy for the Libyan populace and their associated displaced populations. Both the literature and KHCC’s data demonstrated that breast and GIT cancers were among the most prevalent cancers affecting this vulnerable population ( 22 , 24 ). However, screening activities and their associated scale are extremely limited within Libya.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In absence of a well-established national Libyan cancer registry ( 12 ), the results of this study might lay the groundwork for the drafting and development of a cancer care strategy for the Libyan populace and their associated displaced populations. Both the literature and KHCC’s data demonstrated that breast and GIT cancers were among the most prevalent cancers affecting this vulnerable population ( 22 , 24 ). However, screening activities and their associated scale are extremely limited within Libya.…”
Section: Discussionmentioning
confidence: 99%
“…Screening programs should be complemented by simple cost-effective measures as to increase their effectiveness and reach within the population. Awareness campaigns for cervical cancer were already launched in many Libyan cities as of 2020 and adopted a digital format as of 2021 ( 24 ). Such campaigns must be sustained and extended to other prevalent cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation